Investigation of the Effect of Heat Moisture Treatment on Local Sweet Potato Starch Characteristics - . Zaidiyah; Lukman Hakim (Syiah Kuala University, 2015)
The aimed of this study was to determine the effect of Heat Moisture Treatment (HMT) method on the characteristics of local sweet potato starch. Sweet potato starch were isolated from three varieties, namely based on their flesh colour white, light yellow and purple. The native sweet potato starch clasified into two groups; non HMT groups and HMT groups. The native sweet potato starch with HMT treatment were adjusted to moisture content of 25% and exposed to HMT at 110°C for 3 h. The native and treated starches were characterized for starch physicochemical characteristics espescially total dietary fibre (TDF) which is increased significatly